Public Trust: Dampak Exclusion dan Inclusion Error Data Program Keluarga Harapan - Karolus Tatu Sius; Yasinta Y Palan Peten; Kresensia Vemmilia Raju; Hendrikus L Kaha; Frans Nyong (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The general objective of the Family Hope Program (PKH) is to reduce poverty, increase the accessibility of poor people to public services, especially education and health. PKH targeting is based on Integrated Social Welfare Data (DTKS) which is an update of the results of the Social Protection Program Data Collection (PPLS). Efforts to improve the welfare of the poor often stumble over fundamental problems related to data collection. Problems that arise from data not being in sync are inclusion errors and exclusion errors. As a result, the aid distributed is not on target and does not even fulfill the citizens' sense of justice. As a result, the level of public trust in the government decreases. This research aims to obtain an overview of the impact of data collection on public trust. This research uses a qualitative approach with data collection methods using interviews and secondary data analysis. The research results show that there are still very poor household (RTSM) in Cunca Lolos Village that have not yet become beneficiary group (KPM) PKH. This exclusion error occurs because the data collection and data updating process has not been carried out in the DTKS. The impact on the issue of public trust among citizens. Those who are eligible but are not targeted by the program consider the government to be unfair in its services and policies. Finally, citizens do not participate actively in public activities.